THE EFFECT OF PROGRESSIVE MUSCLE RELAXATION AND LAVENDER AROMATHERAPY ON ANXIETY IN PROSPECTIVE IMPLANT CONTRACEPTORS - Vita Triani Adi Puteri; Maftuchah Maftuchah; Sumiyati Sumiyati (Universitas Karya Husada Semarang, 2026)
The implant, also known as a subcutaneous contraceptive rod, contains levonorgestrel (two-rod implant) and etonosgestrel (one-rod implant). Implant contraception has many advantages, but many acceptors are reluctant to do it because they are afraid and anxious about the installation. This contraceptive is 99.8% effective and has a lifespan of 3 years. The first-year failure rate is between 0.2 and 0.5 per woman, making it effective in preventing pregnancy and subsequently controlling population growth.One of the effective non-pharmacological treatments for overcoming anxiety is progressive muscle relaxation therapy and aromatherapy lavender. Progressive muscle relaxation can produce the hormone epinephrine so it can reduce anxiety. Lavender aromatherapy functions to create a relaxing effect so it can reduce anxiety.Based on the research journal of Masdiana & Phonna (2023) and Dewi dkk (2024), both of these treatments are very effective in reducing anxiety because they both function relaxing effect. The research design used in this study was a quasi-experimental study with a one group pretest posttest design. The Wilcoxon test results indicate that progressive muscle relaxation and lavender aromatherapy have an effect on anxiety in prospective contraceptive implant recipients at the Kandeman Batang Community Health Center. It is hoped that the results of this study will be useful for reducing anxiety of prospective KB implant acceptors.